Friendship and the new politics: beyond community. Issue 4 (2nd October 2018) - Nordin,; Smith,
Abstract : ABSTRACT What role can friendship play in contemporary politics? This article answers this question by showing how friendship supplements one of the central tropes of modern European thought: community. It argues that both the recent phenomenon of populism and more traditional political practice rely on this trope. This results in a politics which focuses on identity and difference, inclusion and exclusion. Ultimately this form of politics seeks an immanence which is impossible to achieve. In contrast, friendship offers a new way of thinking about politics as it focuses on open-ended relations between persons based not on sameness, but otherness and difference. The article articulates five key features of this understanding of friendship: (1) that it is a relationship, (2) between self and other, (3) which exists between the friends, which is (4) extendable into a network but not a unity and (5) it eschews all programmes or projects. In this way, friendship suggests not a project or a programme but an ethos. This article concludes by claiming that friendship is the open-ended and ongoing encounter with the other, and its politics holds a shared space open for the potential that this encounter brings.